The multi-model, metadata-driven approach to content and layout adaptation - CONLAN, OWEN; WADE, VINCENT PATRICK (My University, 2004)
Delivering content adapted to not only an end user's needs and preferences, but also to their context and environment presents a number of research challenges. The multi-modal nature of content delivery coupled with the diversity of interests and requirements of a user means that a large number of techniques and mechanisms may need to be employed to tailor the content delivered. However, it is important that the research for related fields should be leveraged to maximum effect. This paper introduces the high level techniques employed in Adaptive Hypermedia and in particular focuses on the Multi-model, Metadatadriven approach to Content Adaptation developed in Trinity College, Dublin.
PUBLISHED
Keywords: Computer Science